PENERAPAN METODE WAWANCARA KLINIS BERBANTUAN ANIMASI POWTOON DALAM MATERI BILANGAN PECAHAN PADA MAHASISWA FKIP PGSD UNTAN - Siti Roisah; Ahmad Yani T; Nurfadilah Siregar (JP2M (Jurnal Pendidikan dan Pembelajaran Matematika), 2025)
Mathematics is a very important main subject. Mathematics is an important topic. The science that must be studied is mathematics. One of the things studied is numbers. Based on previous observation data, it shows below 50% to achieve KKTP in this material. Meanwhile, students as prospective teachers or educators need to know what mathematics material students find difficult. To achieve this, there is a need for innovation in mathematics learning to help students understand fractional number material. The innovation in question is Powtoon animation. The research method is quantitative research and the type of research is uasi-experimental. The design is post-test design only. The data shows : (1) there are differences in the Criteria for Completion of Learning Objectives (KKTP) and the application of the clinical interview method assisted by Powtoon animation in students fractional numbers material on PGSD FKIP students Tanjungpura University and (2) the percentage who achieved the KKTP in the the application of the clinical interview method assisted by Powtoon animation in students fractional number material on PGSD FKIP students of Tanjungpura University is higher than the percentage of not achieveing the KKTP. The author found when applying the clinical interview method that each students had different abilities and interest in subjects, some of the material has been delivered and some admitted that it had not been delivered, this influencing the difference between the Criteria foe Completion of Learning Objective (KKTP) and application of the interview clinical method assisted by Powtoon animation and the percentage profile of those who achieved the KKTP was higher than those who did not achieved the KKTP was higher than those who achieved the KKTP was higher than those who did not achieved the KKTP.